PHARMACOKINETICS AND MOLECULAR DOCKING-BASED INVESTIGATION OF BIOACTIVE COMPOUNDS FROM Curcuma longa TARGETING KEY PROTEINS IN LOW BACK PAIN MANAGEMENT (The Research of Medical Science Review, 2025)
Low back pain (LBP) is a leading health issue throughout the world. It results from several contributing factors including muscle strain, structural problems, arthritis, and disk injuries. Many times, LBP is linked with side effects of conventional pharmacological treatments including NSAIDs and opioids, calling for the safer alternatives. Curcumin and demathoxycurcumin are bioactive natural compounds of Curcuma longa and both of these compounds are known to reduce inflammation and ease pain. This study is designed to investigate the role of these compounds in the treatment the LBP as alternatives of synthetic medicines. This study used pharmacokinetics analysis and molecular docking to test how well these compounds could be used as medicines to target the key proteins involved in LBP. To study pharmacokinetics characteristics of these natural compounds the online servers including Swiss ADME, STOPTOX and pkCSM, were used. While, the interaction of these compounds with key protein involved in LBP was checked through Maestro 12.5. Results of molecular docking analysis showed significant interaction with residues of these key proteins. Furthermore, this suggests that these compounds can play a significant role in controlling inflammatory pathways in LBP. The ADMET analysis suggested good drug-likeness, demonstrating excellent gastrointestinal absorption, low toxicity, and conformity with Lipinski’s rule of five. These compounds showed low blood brain barrier permeability, though, with would limit the central nervous system effects. Furthermore, NMA analysis showed stable bindings between these two compounds and target proteins suggesting that both of these compounds could be the useful natural alternatives for controlling LBP.